Starting Positive: The Impact of Self-Presentation Concerns on Consumer Reviews - Solinas, Elisa; Valsesia, Francesca; Nunes, Joseph C; Ordanini, Andrea (Journal of Consumer Research, 2026)
Abstract This research investigates how reviewers’ self-presentation strategies influence their posting behavior. We find reviewers are less likely to post negative reviews early in their review history due to concerns that doing so would make them appear as lacking warmth. This concern diminishes as the number of reviews associated with their profile increases, resulting in a discernable negative trend in ratings at the reviewer level. We document this trend across two well-known review platforms (Yelp and TripAdvisor). A series of controlled laboratory studies replicate the effect while demonstrating the role played by self-presentation concerns in explaining the downward trend of ratings. Specifically, we find that concerns about appearing to lack warmth influence reviewers’ initial reluctance to post negative (but not positive) reviews, whereas concerns about appearing competent do not. We identify two theoretically consistent managerial interventions that moderate the effect. Allowing reviewers to rate experiences without associating a review with their profile reduces the effect of the number of prior reviews on their likelihood to post, as does prompting them to mention one positive element in their written comments. Our findings underscore the common concern that online review platforms provide positively skewed ratings and offer insight into how to address this.